PENGARUH TRANSFORMATIONAL LEADERSHIP DAN MOTIVASI TERHADAP KINERJA GURU SD DI AL-KAUTSAR KOTA TANGERANG [INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND MOTIVATION ON THE PERFORMANCE OF PRIMARY SCHOOL TEACHERS IN AL-KAUTSAR KOTA TANGERANG] - Dewi Putri Rezekiah (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
Good leadership is leadership that is able to create a smooth implementation of organizational programs and realize organizational goals effectively and efficiently. This study aims to determine the effect of transformational leadership and work motivation on teacher performance at SDI Al Kautsar Tangerang City during academic year 2017/2018. This research is a survey with a quantitative approach. The subject of the research is the teacher while the object of research is the leadership performance and the performance of the principal management of SDI Al Kautsar Tangerang City. The sampling technique used in this study is population. The data collection technique used by the researchers is the method of Questionnaire. The assumption test is Smart-PLS. Hypothesis test using Smart-PLS analysis.